Sero-prevalence of Toxoplasma Gondii in Two Migrating Lore and Khamseh Tribes in Southern Iran: - Mehrabani, Davood; Motazedian, Mohammad Hossein; Asgari, Qasem; Mehrabani, Golnoush (Galen Medical Journal, 2014)
Background: Toxoplasmosis is a zoonotic disease which occurs mostly through ingestion of tissue cysts or oocyst excreted by infected cats. This study was conducted to determine the sero-prevalence of toxoplasmosis in two migrating Lore and Khamseh tribes in southern Iran living in tents with their domestic animals.Materials and Methods: During 2010, using cluster random sampling method, 357 blood samples were collected from two migrating tribes (Khamseh and Lore) in both genders and age groups of 8-80 years in Fars Province, southern Iran. Samples were tested for prevalence of toxoplasmosis using IgG Indirect Fluorescent Antibody Technique (IFAT). Findings in both tribes were compared regarding age, sex and lifestyle.Results: Prevalence of toxoplasmosis among both tribes was 12.3%. There was a significant difference for prevalence of toxoplasmosis between Khamseh (15.6%) and Lore (6.77%) tribes. No significant difference was observed between males (14.3%) and females (10.8%). The rate of infection increased with age. The highest prevalence was seen among those who used unhygienic water from well (15.7%). No relationship was observed between the prevalence of toxoplasmosis and the rate of abortion. In our study, sero-prevalence was lower than other studies in Iran.Conclusion: It seems that lifestyle trends like low consumption of vegetables and absence of cats in their lives are the most important factors for this low prevalence. This infection may be due to their lifestyle of consuming undercooked barbecue meat.[GMJ. 2014;3(4):238-44]